Stiletto Socialism: Social Class, Dressing Up, and Women's Self-Positioning in Socialist Slovenia. Issue 1 (1st March 2020) - Sitar, Polona
Abstract: This article explores how women interpreted everyday clothing practices and decoration of their body and how they positioned themselves in different social milieus during the period of socialist Slovenia (1945–1991). The new socialist middle class in Slovenia and Yugoslavia was defined by participation in a lifestyle, created and expressed through consumption and behaviors that turned everyday life into a symbolic display of taste and cultural distinction. This article shows the ways women engaged in self-expression and negotiated dressing up. It analyzes the self-emancipation of women as they challenged the boundaries of social hierarchies on the basis of self-transformations, pointing out the active role that women had in their self-positioning in social categories.